Examining the assistant principalship : new puzzles and perennial challenges for the 21st century - Shoho, Alan R.; Barnett, Bruce G.; Tooms, Autumn K. (International research on school leadership., 2012)
This edited book highlights the importance and complexity of the assistant principalship. As noted in all the chapters, the assistant principal is a critical partner in creating a professional learning community that serves all students well. Often neglected or ignored in the literature, assistant principals are more than disciplinarians and student or building managers. In the best of all worlds, they provide the professional support and partnership with their principals to create high-performing schools. Unfortunately, as noted in some of the chapters, the ideal and actual roles that assistant principals exercise often create a gap that seethes with disillusionment and dissatisfaction. The challenge for the profession is to better align the roles and expectations of assistant principals so that they can experience the best of being a school leader.